Pengungkapan Tanggung Jawab Sosial Perbankan Syariah di Asia Tenggara - Maesya’bani Maesya’bani; Sri Mulyati; Erina Maulidha (Jurnal Akuntansi dan Keuangan Islam, 2019)
This study aims to measure the social responsibility disclosure of Islamic Bank inSoutheast Asia based on ISR index. The research method in this study is descriptivequalitative with content analysis in annual reports published on the website. Thepopulation in this study is Islamic banking in Indonesia, Malaysia and BruneiDarussalam from 2015-2017. The selected sample used a purposive samplingtechnique consisting of 20 selected Sharia Banks. The results showed overall, thepredicate level of disclosure of sharia banking social performance in Southeast Asiawas considered less informative with a score of 55.35%. Although the level ofdisclosure of social performance continues to increase every year.